APPLICATION OF IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD FOR GENDER BASED PUBLIC TRANSPORTATION PLANNING IN CORRIDOR I BUS RAPID TRANSIT SEMARANG CITY - Landung Esariti; Kharunia Putri; Hadi Wahyono (Jurnal Pengembangan Kota, 2020)
Gender-based public transport planning ensures accommodation of user group preferences to minimize inequality and discrimination among passenger needs. In the practice of accessing BRT Corridor I in Semarang City, it was identified that there were 3 aspects that determined the gap, namely: security, comfort, and accessibility. Importance Performance Analysis is used to describe the level of access gap by comparing service performance provided with passenger expectations. Of 70 respondents answered, 53 women and 17 men, two findings can be concluded. First, it was found that the value of disparity in male and female user groups was equally negative (-) which meant that services received by users were less than expected, with greater levels of access gaps for female user groups compared to male user groups with the value of the gap in women is -0.67 and in men -0.52. This shows that the problem of inequality in the female user group is more urgent to be addressed to meet adequate transportation needs and minimize the access gap that occurs in the female user group. Second, the main priority needs for handling access gaps in the female user group include accessibility aspects and comfort aspects, while in the male user group only the accessibility aspect is concerned. The role and purpose of the movement conducted are two key factors in priority differentiation.